2021
DOI: 10.3389/fmars.2021.711108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-fouling Efficacy of Bacillus licheniformis Extracts Under Environmental and Natural Conditions

Abstract: There is an increasing interest in developing innovative coatings and testing natural products with anti-fouling activity to substitute current highly toxic biocides that have a harmful impact on marine organisms. Bacillus licheniformis species have shown different anti-biofilm and anti-fouling activities in vitro, but so far, its efficacy in field trials has not been tested. For this purpose, the capacity of different extracts of B. licheniformis NCTC 10341T to prevent micro and macro-fouling was first tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Natural antifouling compounds obtained from invertebrates, plants, and microorganisms have also been proposed as one of the best alternatives to current chemical formulations in marine paints and coatings [ 66 , 67 , 68 , 69 , 70 , 81 ]. Antifouling mechanisms of these compounds may be related to alterations in protein expression (e.g., by promoting the underexpression of proteins related to adhesion and biofilm development), oxidative stress induction, neurotransmission blocking (caused by, for example, the inhibition of acetylcholine esterase activity, which interrupts cholinergic signaling and reduces the success of the settlement of fouling organisms), surface modification (e.g., by blocking the attachment site of bacteria), and biofilm inhibition through different mechanisms.…”
Section: Marine Antifouling Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural antifouling compounds obtained from invertebrates, plants, and microorganisms have also been proposed as one of the best alternatives to current chemical formulations in marine paints and coatings [ 66 , 67 , 68 , 69 , 70 , 81 ]. Antifouling mechanisms of these compounds may be related to alterations in protein expression (e.g., by promoting the underexpression of proteins related to adhesion and biofilm development), oxidative stress induction, neurotransmission blocking (caused by, for example, the inhibition of acetylcholine esterase activity, which interrupts cholinergic signaling and reduces the success of the settlement of fouling organisms), surface modification (e.g., by blocking the attachment site of bacteria), and biofilm inhibition through different mechanisms.…”
Section: Marine Antifouling Strategiesmentioning
confidence: 99%
“…The advantages of marine antimicrobial peptides include their stability in high salt concentrations and a range of temperatures (4 °C to 20 °C) [ 86 ]. Additionally, the use of extracts instead of purified compounds previously identified as active molecules could be a suitable approach due to lower production costs and the possibility of having different bioactive compounds in the same extract that may act synergically on different targets of fouler organisms [ 71 , 81 ].…”
Section: Marine Antifouling Strategiesmentioning
confidence: 99%
“…B. licheniformis belongs to the Bacillus subtilis subgroup and is relevant in the search for bioactive compounds (Kaspar et al 2019). Several studies have reported high antifouling activity potential in bioactive compounds from B. licheniformis (Ortega-Morales et al 2008;Aguila-Ramírez et al 2014;Eduok et al 2015;Muras et al 2021a). Many species have been isolated from soft corals with a demonstrated ability to produce compounds with antifouling activity (Pham et al 2016;Hou et al 2019;Abdulrahman et al 2022a;Abdulrahman et al 2022b , Ba-akdah & Satheesh 2021.…”
Section: Tablementioning
confidence: 99%
“…The Bacillus licheniformis strain isolated from Spongia officinalis (marine sponge) has been reported to produce exopolysaccharides, which can reduce the development of biofilm for several bacteria [ 22 ]. Moreover, Muras et al [ 23 ] proposed that B. licheniformis NCTC 10341 can prevent biofilm and soft fouler attachment to non-targeted organisms. Several bioactive compounds in antifouling have been isolated from marine organisms, including corals, sponges, ascidians, bryozoans, and marine microorganisms [ 24 ].…”
Section: Introductionmentioning
confidence: 99%